Case of bullous pemphigoid coexisting with anti‐desmoglein autoantibodies. Issue 7 (24th March 2017) - Tie, Duerna; Yoshida, Tokiko; Chinuki, Yuko; Da, Xia; Ishikawa, Noriyoshi; Morita, Eishin
Abstract: A 79‐year‐old Japanese woman had clinical and histopathological features of bullous pemphigoid, while direct immunofluorescence test revealed C3 and immunoglobulin G depositions in the lower cell surfaces of the epidermis in addition to those in the dermoepidermal junction. Chemiluminescent enzyme immunoassays were positive for desmoglein‐1 and ‐3 antibodies in addition to anti‐BP180 antibodies. In an immunoblotting study, antibodies against both 180‐kDa bullous pemphigoid antigen and 130‐kDa pemphigus vulgaris antigen were detected. Based on these results, bullous pemphigoid coexisting with anti‐desmoglein autoantibodies was diagnosed in this case.